Lactate promoted cisplatin resistance in NSCLC by modulating the m6A modification-mediated FOXO3/MAGI1-IT1/miR-664b-3p/IL-6R axis - Bo, Wei; Yu, Ning; Wang, Xiaokai; Wang, Chun; Liu, Chunying (Neoplasia (New York, N.Y.), 2024)
Cisplatin resistance is one of the major obstacles in non-small cell lung cancer (NSCLC) treatment. Intriguingly, elevated lactate levels were observed in cisplatin-resistant cells, which spurred further investigation into their underlying biological mechanisms. Lactate levels were measured by lactate detection kit. Cisplatin-resistance NSCLC cells were established using progressive concentration of cisplatin. Cell viability, proliferation, and apoptosis were detected by CCK-8, EdU, and flow cytometry, respectively. Cell proliferation in vivo was determined by immunohistochemistry of Ki67 and apoptotic cells were calculated by the TUNEL. MeRIP-PCR was used to measure FOXO3 m6A levels. The interactions of genes were analyzed via RIP, ChIP, Dual-luciferase reporter, and RNA pull-down, respectively. Elevated lactate levels were observed in both NSCLC patients and cisplatin-resistance cells. Lactate treatment increased cisplatin-resistance cell viability in vitro and promoted tumor growth in vivo. Mechanistically, lactate downregulated FOXO3 by YTHDF2-mediated m6A modification. FOXO3 transcriptionally reduced MAGI1-IT1 expression. FOXO3 overexpression inhibited the lactate-induced promotion of cisplatin resistance in NSCLC, which were reversed by MAGI1-IT1 overexpression. MAGI1-IT1 and IL6R competitively bound miR-664b-3p. FOXO3 overexpression or MAGI1-IT1 knockdown repressed lactate-mediated cisplatin resistance in vivo. Lactate promoted NSCLC cisplatin resistance through regulating FOXO3/MAGI1-IT1/miR-664b-3p/IL6R axis in YTHDF2-mediated m6A modification.